Nice shot, Cupid! : Myth-O-Mania #4 - McMullan, Kate; Zilber, Denis (Mankato, Minn. : Stone Arch Books, 2012)
In this updated version of Greek mythology, Hades, King of the Underworld, tells how a gawky teen Cupid fell in love with the mortal Psyche and what really happened when he kidnapped her.
Keywords: Psyche (Greek deity) -- Juvenile fiction; Cupid (Roman deity) -- Juvenile fiction; Hades (Greek deity) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Psyche (Greek deity) -- Fiction; Cupid (Roman deity) -- Fiction; Hades (Greek deity) -- Fiction; Mythology, Greek -- Fiction; Psyche (Greek deity) -- Fiction; Cupid (Roman deity) -- Fiction; Hades (Greek deity) -- Fiction; Greek mythology -- Fiction; Humorous fiction; Humorous fiction